Controlling ve stavebním podniku - Bartizal, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Předmětem diplomové práce je přispět k vylepšení controllingového systému ve stavebním podniku. Hlavní důraz je kladen na využití vhodných nástrojů controllingu, které by měli pozitivní vliv na hospodaření konkrétního podniku. Diplomová práce analyzuje oblast controllingu v akciové společnosti XYZ, a.s. V úvodu je vymezen pojem řízení podniku, controlling a jeho teoretická východiska, dále je popsán současný stav činností controllingu ve firmě. V poslední části diplomové práce jsou navrženy činnosti pro zlepšení fungování controllingového systému včetně zhodnocení přínosů pro daný podnik.

The subject of this thesis is to contribute to the improvement of controlling system in the construction company. The main emphasis is on the use of appropriate controlling tools, which would have a positive impact on the management of a particular enterprise. The thesis analyzes the area of controlling stock in XYZ Company, Inc. The introduction defines the concept of business management, controlling and its theoretical basis, further describes the current activities of the controlling company. In the last part of the thesis proposed actions to improve the functioning of the controlling system, including the evaluation of the benefits for the company.
Controlling in the construction company
Keywords: řízení podniku; controlling; controllingové nástroje; stavební podnik; plán; kontrola; reporting; finanční analýza; informační systém; business management; controlling; controlling tools; construction company; plan; control; reporting; financial analysis; information system